Relationship between students learning style and academic achievement / Miceelle Bau Brau and Robica Kalong - Brau, Miceelle Bau; Kalong, Robica (2014)
This chapter will present the background of the study regarding the students’ education achievement, which emphasized on learning style among undergraduate students in Universiti Teknologi Mara (UiTM) Sarawak. Sections 1.2 will discuss the background of the study; section 1.3 will state the simple of researches issues. Section 1.4 will explains the research problem and section 1.5 is research questions. Section 1.6 will identified a hypotheses and section 1.7 is the research objectives. Under Section 1.8 will specify a scope for the study and Section 1.9 is the significance of the study. Finally Section 1.10 is on the definition of terms or concepts in learning style and section 1.11 will summary the all point.